Epidemiological, clinical and prognostic profile of childhood acute bacterial meningitis in a resource poor setting - Kuti, Bankole Peter (J Neurosci Rural Pract, 2015)
BACKGROUND: Childhood bacterial meningitis is a neurologic emergency that continues to kill and maims children particularly in developing countries with poor immunization coverage. OBJECTIVE: This study set out to assess the hospital incidence, pattern of presentation, etiologic agents, outcome and determinants of mortality among the children admitted with bacterial meningitis at the Wesley Guild Hospital (WGH), Ilesa. PATIENTS AND METHODS: We carried out a retrospective review of admitted cases of bacterial meningitis in children aged one month to 15 years at the WGH, Ilesa over a three year period by looking at the hospital records. Factors in the history and examinations were compared among survivors and those that died to determine factors significantly associated with mortality in these children. RESULTS: Eighty-one (5.5%) of the 1470 childhood admissions during the study period had bacterial meningitis. Male preponderance was observed and two-thirds of the children were infants. More cases were admitted during the wet rainy season than during the dry harmattan season. Haemophilus influenzae type B and Streptococcus pneumoniae were the leading etiologic agents and ciprofloxacin and ceftriaxone adequately cover for these organisms. Twenty-two (27.2%) of the 81 children died, while 34 (42.0%) survived with neurologic deficits. Children with multiple seizures, coma, neck retraction, hyponatremia, hypoglycorrhachia, turbid CSF as well as Gram positive meningitis at presentation were found to more likely to die (P < 0.05). None of these factors however independently predict mortality. CONCLUSION: Childhood bacterial meningitis often results in death and neurologic deficit among infants and young children admitted at the WGH, Ilesa. Children diagnosed with meningitis who in addition had multiple seizures, neck retraction and coma at presentation are at increased risk of dying.